The Bacterial and Fungal Gut Microbiota of the Greater Wax Moth, Galleria mellonella L. Consuming Polyethylene and Polystyrene - Ruiz Barrionuevo, Juliana M.; Vilanova-Cuevas, Brayan; Alvarez, Analía; Martín, Eduardo; Malizia, Agustina; Galindo-Cardona, Alberto; de Cristóbal, Ricardo E.; Occhionero, M. Angelica; Chalup, Adriana; Monmany-Garzia, A. Carolina; Godoy-Vitorino, Filipa (Frontiers in Microbiology, 2022)
Plastic production has been increasing exponentially in the last 60 years, but plastic disposal is out of control, resulting in the pollution of all ecosystems on Earth. Finding alternative environmentally sustainable choices, such as biodegradation by insects and their associated gut microbiota, is crucial, however we have only begun to characterize these ecosystems. Some bacteria and one fungus have been previously identified in the gut of Greater Wax Moth larvae (Galleria mellonella L., Lepidoptera, Pyralidae) located mainly in the Northern hemisphere. The aim of this study was to describe changes in the gut microbiota associated with the consumption of polyethylene and polystyrene by the Greater Wax Moth in Argentina, considering both bacteria and fungi. Larvae were fed polyethylene, polystyrene and beeswax as control for seven days. Next generation sequencing revealed changes in the bacterial gut microbiome of the wax moth larvae at the phyla and genus levels, with an increase in two Pseudomonas strains. The fungal communities showed no differences in composition between diets, only changing in relative abundance. This is the first report of both bacterial and fungal communities associated with a plastivore insect. The results are promising and call for more studies concerning a potential multi-kingdom synergy in the plastic biodegradation process.